2019
DOI: 10.1177/0022002719887492
|View full text |Cite
|
Sign up to set email alerts
|

Child Discipline in Times of Conflict

Abstract: Using a unique pairing of household survey data and geolocational conflict data, we investigate the relationship between conflict intensity and the disciplinary methods employed by Iraqi households. We find that parents in high-conflict areas are more likely to use moderate and severe corporal punishment and are less likely to use constructive parenting techniques like redirection. A corresponding difference-in-differences analysis confirms the nature of this association. While there is a general sense that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Mediation analysis also showed that mothers' disciplining partly explained the association between conflict intensity and children's and adolescents' functioning problems. Our results are line with the findings of previous studies with Iraq samples showing the association between conflict intensity and harsh discipline (Malcolm et al, 2020) and the association between maternal discipline and child functioning (Logan et al, 2022). Using two different waves of MICS Malcolm et al (2020) found that casualty rates were associated with decreased use of positive discipline and increased use of harsh discipline among Iraqi mothers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mediation analysis also showed that mothers' disciplining partly explained the association between conflict intensity and children's and adolescents' functioning problems. Our results are line with the findings of previous studies with Iraq samples showing the association between conflict intensity and harsh discipline (Malcolm et al, 2020) and the association between maternal discipline and child functioning (Logan et al, 2022). Using two different waves of MICS Malcolm et al (2020) found that casualty rates were associated with decreased use of positive discipline and increased use of harsh discipline among Iraqi mothers.…”
Section: Discussionsupporting
confidence: 92%
“…Although our research used geolocational data for conflict exposure as a predictor, physical proximity, perceived level of stress, personal traumatic experiences, the duration and type of the conflict can also be influential factors. Finally, similar to Malcolm et al (2020), the study did not have individual-level longitudinal data nor an experimental design with random assignment, which constitute a causality issue. There may be bidirectionality in the associations, as such difficult children may be getting more severe forms of punishment from their parents or households were not placed randomly on high or low conflict areas.…”
Section: Discussionmentioning
confidence: 99%
“…They differ in which conclusions are currently being evoked by the experiences and inputs they are receiving. A parallel example comes from child discipline in wartime (Malcolm et al, 2020). In communities exposed to warfare, parents discipline their children in more coercive ways.…”
Section: Discussionmentioning
confidence: 99%
“…We then use these death rates to construct a treatment variable that is equal to one if a governorate experienced high conflict during the respective period and equal to zero if the governorate did not experience high conflict. 3 Following Diwakar et al (2019), Malcolm et al (2020) and Naufal et al (2019), we define high conflict as the 75 th percentile of conflict-related civilian death rates within the distribution of death rates across all governorates for that specific year. In other words, the treatment variable is one for a household residing in a governorate where the number of conflict-related civilian deaths per 1000 residents is higher than the death rate for the 75 th percentile of all governorates for that year.…”
mentioning
confidence: 99%
“…The generalized difference-in-differences estimator described by Hansen (2022) allows for more than two periods and also allows for governorates to switch between the treatment and control groups across periods, which gives us the opportunity to better exploit the evolution in the nature of the Iraqi conflict over time as an explanatory variable. Note that our model expands on existing work on armed conflict in Iraq, which uses simple difference-in-differences (Cetorelli, 2015;Malcolm et al, 2020;Naufal et al, 2019). Explicitly, the baseline model is:…”
mentioning
confidence: 99%